1983
DOI: 10.1038/icb.1983.12
|View full text |Cite
|
Sign up to set email alerts
|

Fallopian Tube Microvasculature in the Rabbit

Abstract: Summary, the microvascular architecture of rabbit Fallopian lube isthmic, ampuliary and fimbrial regions was examined by the corrosion vascular caslscanning electron microscope method. The aorla and inferior vena cava of virgin adult female rabbits (25-3-5 kg) were cannulated; after blood wash oul. methacrylate casting medium was infused via the aorta. After plastic hardening. Fallopian lubes were excised, tissues corroded and casts prepared for scanning electron microscopy. The isthmic myosalpinx is encircled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
2

Year Published

1983
1983
1994
1994

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 1 publication
1
19
2
Order By: Relevance
“…lb) [Verco et al, in press]. This contrasts markedly with our current observations in pregnant rabbits and observations of control oviduct MVA [Verco et al, 1983a]; that there are any changes in tubal MVA at all in pregnancy and after ovariectomy implies a relationship between tubal microvasculature and local or circulating ovarian and placental hormones. Greiss and Anderson [1970] reported that estradiol caused marked uterine vasodilation in ewes (although during prolonged administration resistance developed); progesterone seemed to sensitize the vascular bed to estradiol.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…lb) [Verco et al, in press]. This contrasts markedly with our current observations in pregnant rabbits and observations of control oviduct MVA [Verco et al, 1983a]; that there are any changes in tubal MVA at all in pregnancy and after ovariectomy implies a relationship between tubal microvasculature and local or circulating ovarian and placental hormones. Greiss and Anderson [1970] reported that estradiol caused marked uterine vasodilation in ewes (although during prolonged administration resistance developed); progesterone seemed to sensitize the vascular bed to estradiol.…”
Section: Discussioncontrasting
confidence: 57%
“…The changes observed in fimbrial core MVA in this study which contrast so markedly with control fimbrial core MVA [Verco et al, 1983a] and that reported after ovariectomy [Verco et al, in press] suggest a particular sensitivity of tubal microvasculature to ovarian or pla cental hormones and. using a similar argument to that developed above, indicates the potential for fimbrial venous distension around the time of ovulation.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Verco et al [1983] described the rabbit uterine tube microvascular architecture (MVA) and speculated on the role of the tubal microvas culature in tubal gamete transport; they sug gested that the large interlocking isthmic subserosal vascular plexus had the potential, if distended, to act as an extramyosalpingeal sphincter. In addition, they proposed that the large and frequent ampullary plical veins may indicate a large local capacity for inter stitial and perhaps also ampullary luminal fluid absorption which could modify fluid flow along the tube.…”
Section: Introductionmentioning
confidence: 99%